Actors in Environmental Discourse: The Discursive Institutionalism Perspective - Mirzyńska, Anna (Journal of Public Governance, 2023)
Objective: Examined for years in various contexts, the environmental issue does not directly focus on the involve- ment of actors in the process of discourse institutionalisation, which is achievable through the application of discursive institutionalism. The aim of the study is to characterise actors involved in the environmental discourse studied using the discursive intuitionalism approach: who participates in discourses, with whom they co-participant, and based on which sources of discourse records their presence is studied.Research Design & Methods: A systematic review examined 185 DI articles from 2004 to 2022, selecting 33 focused on environmental topics for content analysis.Findings: Seven actor groups in environmental discourse were identified, with government, experts, and NGOs being the most frequent participants. Government predominated in co-occurrence, and discourse records mainly originated from government documents, legislative materials, and reports.Implications/Recommendations: Further research is recommended to delve into actor profiles, explore the relationship between discourse source selection and actor appearance, and observe trends in DI research methods. Emphasising inclusive representation in environmental discourse is crucial for policymakers.Contribution/ Value Added: Participation in environmental discourse is dominated by actors with specialised knowledge or resources, responsible for shaping political agenda goals. This results in low representation of unaffiliated citizens, business, and media.Article classification: research articleKeywords: environmental discourse, environmental policy, discursive institutionalism, actors, environmental economicsJEL classification: Q5, H8